CXCL12 Induction of iNOS in Human CD8 T Cells - Choy, Jonathan C. (2008)
BACKGROUND: We reported previously that inducible nitric oxide synthase (iNOS) expression in graft-infiltrating human T cells, which is confined to the bystander population, contributes to T cell-mediated rejection of allograft arteries in a humanized mouse model. Here, we examine if CXCL12, a chemokine thought to contribute to recruitment of bystander T cells, induces iNOS in human CD8 T cells. METHODS: Human CD8 T cells were treated with CXCL12 and iNOS expression examined. Also, human allograft arteries were immunohistochemically stained for iNOS and CD8, and adjacent sections stained for CXCL12 to determine their localization in human tissues. RESULTS: Resting human CD8 and CD4 T cells expressed the CXCR4, but not the CXCR7, receptor for CXCL12. Treatment with CXCL12 induced expression of both iNOS mRNA and protein in primary human CD8 T cells in a dose-dependent manner, but had no effect on CD4 T cells. Induction of iNOS expression in CD8 T cells was mediated by increased gene transcription. TCR-activated CD8 T cells rapidly down-regulated CXCR4 and this coincided with diminished ability of CXCL12 to induce iNOS in activated T cells. iNOS expression in infiltrating human CD8 T cells was spatially associated with CXCL12 expression both in the humanized mouse model of allograft artery rejection and in clinical specimens of coronary arteries displaying allograft vasculopathy. CONCLUSIONS: CXCL12 induces iNOS expression in human CD8 T cells and this response may contribute to allograft rejection.